MicroRNA-212 inhibits hepatocellular carcinoma cell proliferation and induces apoptosis by targeting FOXA1 - Tu, Huahua (Onco Targets Ther, 2015)
MircroRNA-212 (miR-212) is proposed as a novel tumor-related miRNA and has been found to be significantly deregulated in human cancers. In this study, the miR-212 expression was found to be obviously downregulated in hepatocellular carcinoma (HCC) tissues as compared with adjacent nontumor tissues. Clinical association analysis indicated that low expression of miR-212 was prominently correlated with poor prognostic features of HCC, including high AFP level, large tumor size, high Edmondson-Steiner grading, and advanced tumor-node-metastasis tumor stage. Furthermore, the miR-212 expression was an independent prognostic marker for predicting both 5-year overall survival and disease-free survival of HCC patients. Our in vitro studies showed that upregulation of miR-212 inhibited cell proliferation and induced apoptosis in HepG2 cells. On the contrary, downregulation of miR-212 promoted cell proliferation and suppressed apoptosis in Huh7 cells. Interestingly, we found that upregulation of miR-212 decreased FOXA1 expression in HepG2 cells. Significantly, FOXA1 was identified as a direct target of miR-212 in HCC. FOXA1 was downregulated in HCC tissues as compared with noncancerous tissues. An inverse correlation between FOXA1 and miR-212 expression was observed in HCC tissues. Notably, FOXA1 knockdown inhibited cell proliferation and induced apoptosis in HepG2 cells. In conclusion, miR-212 is a potent prognostic marker and may suppress HCC tumor growth by inhibiting FOXA1 expression.